Comparison of patient‐specific internal gross tumor volume for radiation treatment of primary esophageal cancer based separately on three‐dimensional and four‐dimensional computed tomography images. Issue 4 (24th June 2013) - Wang, W.; Li, J.; Zhang, Y.; Li, F.; Xu, M.; Fan, T.; Shao, Q.; Shang, D.
Summary To compare the target volume, position and matching index of the patient‐specific internal gross tumor volume (IGTV) based on three‐dimensional (3D) and four‐dimensional (4D) computed tomography (CT) images for primary esophageal cancer. Twenty‐nine patients with primary thoracic esophageal cancer underwent 3DCT and 4DCT scans during free breathing. IGTVs were constructed using three approaches: combining the gross target volumes from the 10 respiratory phases of the 4DCT dataset to produce IGTV10; IGTV2 was acquired by combining the two extreme phases; and IGTV3D was created from the 3DCT‐based gross target volume by enlarging the 95th percentile of motion in each direction measured by the 4DCT. 0.16 cm lateral (LR), 0.14 cm anteroposterior (AP) and 0.29 cm superoinferior (SI) in the upper; 0.18 cm LR, 0.10 cm AP and 0.63 cm SI in the middle; and 0.40 cm LR, 0.58 cm AP and 0.82 cm in the lower thoracic esophagus could account for 95% of respiratory‐induced tumor motion. The centroid position shift between IGTV10 and IGTV2 was all below 0.10 cm, and less than 0.20 cm between IGTV10 and IGTV3D. IGTV10 was bigger than IGTV2; the mean value of matching index for IGTV2 to IGTV10 was 0.87 ± 0.05, 0.85 ± 0.06 and 0.83 ± 0.05 for upper, middle and distal thoracic esophageal tumors, respectively, and just 0.57 ± 0.11, 0.56 ± 0.13 and 0.40 ± 0.03 between IGTV3D and IGTV10. 4DCT‐based IGTV10 is a reasonable patient‐specific IGTV for primary thoracic esophageal cancer, and IGTV2 is considered as an acceptable alternative to IGTV10. However, it seems unreasonable to use IGTV3D substitute IGTV10.